2016
DOI: 10.1007/s10995-016-1978-0
|View full text |Cite
|
Sign up to set email alerts
|

What Do Children with Chronic Diseases and Their Parents Think About Pediatricians? A Qualitative Interview Study

Abstract: Objectives The aim of this study was to determine how pediatric patients and their parents perceive health care during hospital stays, what are their expectations of doctor behaviors, and which components of care do they consider to be the most important. Methods A qualitative descriptive study was carried out using the open interview technique. Twenty-six parents and 22 children undergoing hospital treatment participated. Results Our analysis identified two major themes: (1) doctor verbal and non-verbal behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 21 publications
0
16
1
5
Order By: Relevance
“…While prior studies have emphasized the importance of clear communication with families during FCR ( 5 , 6 , 14 , 15 ), our study demonstrated that parents believe these factors also impact their engagement in the rounding process. One prior study showed, however, that fewer than half of parents understood the plan of care discussed during FCR ( 16 ).…”
Section: Discussioncontrasting
confidence: 60%
“…While prior studies have emphasized the importance of clear communication with families during FCR ( 5 , 6 , 14 , 15 ), our study demonstrated that parents believe these factors also impact their engagement in the rounding process. One prior study showed, however, that fewer than half of parents understood the plan of care discussed during FCR ( 16 ).…”
Section: Discussioncontrasting
confidence: 60%
“…All the mothers in this study described the importance of seeking information to better care for their child’s health. Education was seen as an integral part of a doctor’s role, but often limited in terms of detail, attention or time [ 43 , 44 ]. Patients (and parents) frequently seek their own information, particularly from the internet, to appear more committed to their child’s health; they wanted health providers to listen to their concerns and engage in meaningful discussion about their child’s health [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although not broadly studied, presence of jargon in the clinical context has been evaluated in adult populations to a limited extent, including jargon relating to chief complaint,[12, 15] complex medical terminology,[1619] use of statistics,[20] contextual jargon (lay terms with specific meaning in the clinical context),[19] and provision of explanations. [17, 18, 21, 22] All play a role in creating communication barriers between clinicians and families. For example, a randomized crossover trial found that adult patients with chronic illnesses had better understanding of their conditions when medical terminology was translated in clinical correspondence.…”
Section: Introductionmentioning
confidence: 99%
“…[22] Similarly, studies evaluating parents of children with diabetes and chronic illnesses indicated that parents may misunderstand and resent medical jargon, and endorsed clearer language and communication techniques to allow for parent understanding. [23] [21] Additionally, clinician use of jargon created barriers for the clinician/parent relationship, when parents considered use of language they could not comprehend as an avoidance of direct conversation. [21] Jargon use persists despite findings in research showing evidence of parents’ negative and emotional reactions to clinician jargon,[12, 24] parental lack of understanding of complex language,[2023, 25, 26] and parental difficulty recalling and understanding complex medical dialogue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation